Penguatan Service Learning Melalui Konsep Kepimpinan Tan Malaka Pada Mahasiswa Pascasarjana Manajemen Pendidikan Islam Universitas Islam Negeri Sjech M.Djamil Djambek Bukittinggi - Junaidi, Junaidi; Syam, Hidayani; Syafitri, Widya; Susanti, Mimi; Amna, Lailal (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2023)
This study aims to increase and strengthen as well as strengthen understanding of leadership and behavioral theory in organizations through the leadership of Islamic Education Management, the formation of scientific understanding for students that displays Islamic Education management in the leadership concept of Tan Malaka. The activities carried out are based on reinforcement carried out by Postgraduate students in Islamic Management Education, which are carried out directly at the home of Tan Malaka's birth, and can get to know any historical heritage from Tan Malaka and can directly discuss with the surrounding community. and strengthening the concept of Tan Malaka's leadership given related to the concept of Tan Malaka's leadership. With this strengthening it is able to understand correctly how the concept of leadership from Tan Malaka, the research results obtained from strengthening the concept of Tan Malaka's leadership have a positive influence on students.